2013
DOI: 10.1371/journal.pone.0075685
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Reproductive Outcomes According to Different Serum Anti-Müllerian Hormone Levels in Females Undergoing Intracystoplasmic Sperm Injection

Abstract: Background and aim of the studySerum anti-Müllerian hormone (AMH) is a reliable marker of ovarian reserve, and it has been shown to be correlated with reproductive outcomes in grouped analyses. However, practical data is scarce for the physician and the patients to predict these outcomes in an individual couple according to serum AMH measured prior to assisted reproduction technology (ART) procedures.Study DesignTo address this question, we performed an analytic observational study including 145 females underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Currently, a variety of biochemical and sonographic tests allow this evaluation (Nelson et al, 2007;Lee et al, 2009). Serum levels of FSH and anti-Müllerian hormone (AMH), and the antral follicle count (AFC), are considered baseline factors predicting the ovarian reserve (Nelson et al, 2007;Lee et al, 2009;Fridén et al, 2011;Brugo Olmedo et al, 2013;Li et al, 2016;Yin et al, 2019). The third criterion of the Bologna ESHRE consensus group defines diminished ovarian reserve (DOR) as women presenting either an AFC ≤ 5-7 or an AMH assay ≤ 0.5-1 ng/mL (Ferraretti et al, 2011).…”
Section: Ovarian Reservementioning
confidence: 99%
See 4 more Smart Citations
“…Currently, a variety of biochemical and sonographic tests allow this evaluation (Nelson et al, 2007;Lee et al, 2009). Serum levels of FSH and anti-Müllerian hormone (AMH), and the antral follicle count (AFC), are considered baseline factors predicting the ovarian reserve (Nelson et al, 2007;Lee et al, 2009;Fridén et al, 2011;Brugo Olmedo et al, 2013;Li et al, 2016;Yin et al, 2019). The third criterion of the Bologna ESHRE consensus group defines diminished ovarian reserve (DOR) as women presenting either an AFC ≤ 5-7 or an AMH assay ≤ 0.5-1 ng/mL (Ferraretti et al, 2011).…”
Section: Ovarian Reservementioning
confidence: 99%
“…In the recent years AMH has been shown to represent a reliable marker of ovarian reserve and ovarian stimulation response (Fridén et al, 2011;Brugo Olmedo et al, 2013). Although knowledge of the physiologic role of AMH remains limited, various studies have demonstrated its importance as regulator of ovarian activity (Azizi et al, 2019).…”
Section: Ovarian Reservementioning
confidence: 99%
See 3 more Smart Citations